Prevalence of anxiety and depression in a predominantly HIV-infected population with severe cutaneous adverse drug reactions - Zitha, Eddy (Department of Medicine, 2016)
Background: There is limited data on anxiety and depression in subjects with severe cutaneous adverse drug reactions (SCADR), in a predominantly HIV - infected population. The aim of the study was to prospectively investigate the prevalence of anxiety and depression and quality of life in patients with SCADR. Methods: In this prospective study, SJS, SJS - TEN, TEN and DRESS patients were assessed for anxiety and depression using validated scoring systems, the Hospital Anxiety and Depression Scale (HAD S), and the Dermatology Life Quality Index (DLQI). This was done at six weeks post discharge and again at six months follow - up. Results: Forty - eight patients with SCADR were enrolled at six weeks and 37/48 (77%) completed the study at six months. The populations were similar demographically at six weeks and six months. At six weeks anxiety or borderline anxiety symptoms/caseness was identified in 25/48 (52%) SCADR patients and depression or borderline depression symptoms/caseness in 24/48 (50%). Of those with symptoms, 18 were assessed as having co - morbid anxiety and depression with only 2 cases of pure anxiety and 4 of pure depression. At six months only 37 patients with SCADR returned for follow - up. Four of them had died in the interim while the other seven relocated. Of the cases of pure anxiety; one resolved and one was lost to follow - up. Of the cases of pure depression; one resolved, one persisted, one converted to comorbid anxiety and depression and one was lost to follow - up. Of those with co - morbid anxiety and depression 10 persisted, 2 converted to pure depression, 3 normalised and 2 were lost to follow - up. One previously normal patient developed anxiety symptoms and one case developed comorbid anxiety and depression. In 9/13 (69%) of the patients with SJS, SJS - TEN and TEN, co - morbid anxiety and depression persisted from week six to 6 months. In contrast in only 1/5 (20%) of the patients with DRESS, co - morbid anxiety and depression persisted from week six to 6 months. The cases of pure anxiety and depression were too small for meaningful comment. The overall SJS, SJS - TEN and TEN had median DLQI 8.4 relative to DRESS (DLQI 7.5) at six weeks. However, TEN (DLQI 14) had a greater impact on the quality of life compared to SJS (DLQI 3) and DRESS (DLQI 7.5). This pattern was maintained at six months. Conclusion: Anxiety and depression in patients with SCADR in a predominantly HIV - infected population is present. In the majority of cases, depression and anxiety coexist in patients with SCADR. These are sustained for at least 6 months post discharge. SCADR has a negative impact on quality of life. Our findings should help to improve the awareness of the impact of severe cutaneous adverse drug reactions on mental health especially as this may impact on future treatment adherence.